Investigation of the effect of drought stress on the rice transcriptome - Zombori, Zoltán (Acta Biologica Szegediensis, 2008)
Abiotic stresses such as drought are very important factors that endanger the crop production and stability. Plant root is the most important organ for uptake of water, therefore it plays important role in tolerance to osmotic and drought stresses. Plants developing stronger and deeper roots suffer less from water deficit. The aim of our work was to understand and improve the drought stress-tolerance in cereals by analyzing the transcriptional changes in the root system of different rice cultivars under drought stress conditions. According to the results of the DNA chip hybridizations the response of the genes to the drought stress is altered in roots during the day. Further experiments showed that the expression patterns of genes in cultivars with distinct levels of stress tolerance are different, and that may correlate to their stress tolerance.